The impact of selected financial variables on major sectoral output in Malaysia and Singapore - Abd. Ghani, Nur Hanim (2002)
This study empirically investigates the impact of four selected financial variables namely money supply, treaswy bill rate, credit supply and exchange rate on major sectoral output such as agriculture, manufacturing and services in Malaysia and Singapore economies. The Granger causality of Vector Error Correction Model (VECM) was utilized in this study. Generally, this study has revealed that money supply, treasury bill rate, credit supply, exchange rate and three major sectoral output in both countries are cointegrated. Hence, the presence of cointegrating vector indicates that these variables stay close to each other and do not drift far apart in the long-run although they may diverge from each other in the short-run. The estimates of the VECM models for the Malaysian agriculture and manufacturing sectors show that the agriculture output, manufacturing output and treasury bill rate are considered as endogenous variables, whereas money supply,credit supply and exchange rate are found to be weakly exogenous. For the Malaysian services sector, the results show that money supply, credit supply and services output variables are endogenous. This implies that these variables adjust to short -run deviations from long-run equilibrium. For the case of Singapore agriculture sector, money supply and agriculture output variables are identified as endogenous variables in the model and the manufacturing output alongside all selected financial variables except credit supply are found important for the short-run adjustment. The exchange rate in the Singapore services sector is identified as weakly exogenous variable. Based on the Granger causality analysis using the VECM framework, the credit supply has a significant effect on all the three major sectors in Malaysia. Treasury bill rate and exchange rate are found to influence the manufacturing and services output performance. Meanwhile, money supply can be used to control the fluctuations in services sector. For the case of the Singapore economy, all four selected financial variables are found to affect all three major sectors. Specifically, the results revealed that there are several significant relationships (bi-directional) namely between treasury bill rate and the agriculture output, between money supply and the manufacturing output and between credit supply and manufacturing output. For the services sector, bi-directional causal relationships occurred between treasury bill rate and the services output, and between exchange rate and services output performance.Overall, the impacts of the financial variables on output performances are specified to the sectors concerned. Therefore, selective policy action could be drawn as appropriate due to non-uniformity of the impact of the financial variables on those sectors.